Performance of Poly-BADGE 2:1 Based Polymer Inclusion Membrane for Selective Transport of Malachite Green: Optimization and Stability Studies - Agung Abadi Kiswandono; Anisa Rahmawati; Marsanda Nur Wahyuningtyas; Jamiatul Akmal; Barlah Rumhayati; Ulfa Andayani; Arifina Febriasari; Annur Valita Sindiani; Hanny Julia Putri; Supratikno Supratikno; Rinawati Rinawati (Journal of Multidisciplinary Applied Natural Science, 2026)
Malachite green (MG) is a persistent and toxic triphenylmethane dye. This dye is widely used in textile industries, contributing to significant contamination of aquatic environments. The development of selective and efficient separation methods for MG therefore remains an important challenge. In this study, MG transport was investigated using a polymer inclusion membrane (PIM) incorporating poly-bisphenol A diglycidyl ether (Poly-BADGE 2:1) as a carrier. The effects of key operational parameters, as well as the presence of competing metal ions (i.e., Pb(II) and Cu(II)), were systematically evaluated. The membrane was prepared using Poly-BADGE 2:1 as the carrier, polyvinyl chloride as the base polymer, and dibenzyl ether as the plasticizer. MG concentration was determined by UV–vis spectrophotometry at 617 nm, while membrane characteristics before and after transport were analyzed using Scanning Electron Microscopy (SEM) and Fourier-Transform Infrared (FTIR) instruments. The results showed that MG transport reached 90.90% under optimal conditions (source phase pH 7, receiving phase 1.25 M HNO₃, membrane thickness T54, carrier concentration 0.09 M, and transport time of 24 h). In the presence of Pb(II) and Cu(II) ions, the transport efficiency decreased to 85.67%, compared to 91.32% without metal ions, suggesting competitive interactions at the carrier sites. These findings demonstrate that Poly-BADGE-based PIMs provide an effective and selective system for MG separation, with good structural stability and promising potential for wastewater treatment applications.